Dalbavancin for infective endocarditis: a single centre experience. (19th May 2021) - Durante-Mangoni, Emanuele; Boccia, Filomena; Ursi, Maria Paola; Karruli, Arta; Andini, Roberto; Galdo, Maria; Zampino, Rosa
Abstract : Infective endocarditis (IE) is a life-threatening disease, mostly caused by gram-positive cocci, needing a 4–6 weeks antibiotic course. Dalbavancin is a lipoglycopeptide active on gram-positive microorganisms, with a unique pharmacokinetic profile. We describe our experience with dalbavancin to complete the intravenous antibiotic regimen for difficult-to-treat IE cases due to gram-positive bacteria. We treated 10 severely ill patients, each presenting several comorbidities. Seven patients were microbiologically cured from IE, but two patients experienced IE relapse due to the same microrganism. Short-term mortality after dalbavancin was nil, but late mortality (within 1 year of hospital discharge) was 60%. No death was related to dalbavancin therapy. Treatment was generally well tolerated. Dalbavancin may be an option to complete IE treatment in selected cases, once blood culture clearance and improvement of clinical conditions under standard therapy is reached, allowing shortening of hospitalization.